Faktor-Faktor yang mempengaruhi peningkatan kualitas pelayanan kesehatan di Rumah Sakit: Tinjauan Teoritis - Sophiana Enjellin Anathasia; Dety Mulyanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Improving hospital service quality is an important factor in promoting service user (patient) satisfaction. In this modern era, where services in the health sector is a promising business. Because service quality influences service user loyalty, service performance must be improved. The goal of this theoretical review is to determine what factors influence hospital service quality. A theoretical review is used, which involves analyzing and comparing existing theories. According to the findings of this theoretical review, tangible, reliable, responsive, assurance, and empathy can all have an impact on service quality.